CONVERGENT (NBIC) TECHNOLOGIES: PROBLEMS OF DEVELOPMENT AND TRANSFORMATIONAL POTENTIAL - И В Данилин (Vestnik RUDN. International Relations, 2017)
Modern innovation policy is formed under strong influence of disruptive technologies con-cepts, which help mobilize support for Science and Technology (S&T) policy, structure international S&T cooperation and system, etc. They are also important for the global processes, promising changes in leading powers cohort. This is why disruptive technology concepts are accented by the emerging economics, especially by BRIC nations. A concept of converging (or nano-bio-info-cognitive, also known as NBIC) technologies is very illustrative. Being originally a part of the USA nanotechnology policy and transhumanistic discourse, it gradually evolved globally with focus on “Grand Challenges”. But, despite successes of technology convergence since 2000s, concept itself proved to be not fully operational, being mostly a metaphor for rising interdisciplinarity and discipline convergence. Nonetheless its revolutionary potential was meaningful, but linked not to technological, but institu-tional and socio-cultural dimensions. Among them were human capital development, changing logic of S&T organization, reforming S&T policies, formation of new culture and ethics of research and development, systemic development of national innovation systems. These ideas, implicitly present in the NBIC concept, were of a special importance for the emerging economies as key factors for their enforced growth and rising quality of development processes. But these issues were surprisingly weak articulated in NBIC concept. Partly that was the influence of transhumanist discourse with its escape from solving societal challenges by technological change of human self. Not less important was that NBIC were seen by elites as a mean to bypass deep reforms and buildup of innovation institutions. I.e., concepts of disruptive technologies represent a psychological sub-stitute for a really intense development. Uniqueness of NBIC is that it makes this contradiction very visible. As shown in analyses of NBIC concept, realization of disruptive technologies concepts need stronger accent on the institutional and structural factors, attention to Grand Challenges, etc. Especially this is true for the emerging economies. Only if complex nature and non-technological aspects of disruptive technologies development are taken in consideration, changes of their role in the global processes may occur.